Effect of mass of solid and soaking effect on chemical component of essential oil of physalis minima linn by solvent-free microwave extraction (SFME): article - Md Nor, Nadirah; Che Radzi, Nurhaslina (2019)
Essential oils extraction from Physalis minima L. plant was performed using the solvent-free microwave extraction (SFME) method. The aim of this research is to study the effect of mass of solid and soaking effect on chemical component of essential oil of Physalis minima Linn were studied. The mass of solid and soaking days applied in this research are 4,6,8,10g and 1,2,3 days, respectively. GC-MS was used in determination of chemical components in the essential oils. It is found that the main constituents identified in relative higher abundance is Lanosta-8,24-dien-3-ol, acetate or known as Lanosteryl acetate. Therefore, it is demonstrated that by increasing the mass of solid, it will isolate more chemical component in essential oil and extending the soaking time reduces the availability of chemical compound in essential oil from P. minima